مفهوم الكلام عند سيبويه وغيره - Abdullah Zainur Rouf (LISANIYAT, 2010)
Born in Syiraz, Imam Syibawaih spent his youth to study various disciplines, especially Arabic syntax, with many Muslim scholars. He defines a proposition (kalam) by giving an example    أخوك عبد الله وهذا أخوك. Referring to this example, Imam Jamaluddin ibn Yusuf defines proposition as “an expression of two aspects, which is the text and meaning.” Meanwhile, according to Syekh Musthafa al-Ghulayaini, a proposition is an utterance constructed from two of more words and meaning, and often defined as sentence. Based on its kinds, sentence can be divided into two parts, i.e., “nominal sentences” and “verbal sentence.” And based on its function, sentence can be divided into six groups, jumlah khabariyah, jumlah haliyah, jumlah maf’uliyah, jumlah na’atiyah, jumlah idhafiyah, and jumlah jazaiyah.